2015
DOI: 10.1111/febs.13235
|View full text |Cite
|
Sign up to set email alerts
|

Drosophilablood cells and their role in immune responses

Abstract: Drosophila melanogaster has been extensively used to study the humoral arm of innate immunity because of the developmental and functional parallels with mammalian innate immunity. However, the fly cellular response to infection is far less understood. Investigative work on Drosophila haemocytes, the immunosurveillance cells of the insect, has revealed that they fulfil roles similar to mammalian monocytes and macrophages. They respond to wound signals and orchestrate the coagulation response. In addition, they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
88
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(94 citation statements)
references
References 153 publications
1
88
0
Order By: Relevance
“…The Wnt/beta-catenin signaling pathway, which is involved in cellular proliferation and differentiation, has also been implicated in insect host-virus interactions, though its role in immune function is less well characterized 73, 74 . Several genes involved in Wnt signaling (e.g., osa ) exhibited increased expression in virus-infected bees (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The Wnt/beta-catenin signaling pathway, which is involved in cellular proliferation and differentiation, has also been implicated in insect host-virus interactions, though its role in immune function is less well characterized 73, 74 . Several genes involved in Wnt signaling (e.g., osa ) exhibited increased expression in virus-infected bees (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The capacity of an adult insect to survive systemic challenge with exogenous microbes depends largely on the efficacy of its cellular immune system, and more specifically, hemocyte-mediated phagocytosis (Hillyer and Strand, 2014; Vlisidou and Wood, 2015). We thus investigated the ability of siOBP6, siGFP and siOBP6 R adults to survive following systemic challenge with 10 3 CFU of E. coli K12.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, we showed that Hfq is required for the maintenance of the persistent infection of E. coli in Drosophila. Hfq seemed to inhibit the killing of bacteria in hemocytes, a major phagocytic cell type in Drosophila (74,75), after engulfment, which should be a mechanistic explanation for the Hfq-mediated persistent infection of E. coli. There was no difference in the efficacy of phagocytosis of E. coli between the parental and Hfq-lacking strains, whereas the Hfq-lacking strain was more rapidly killed in phagocytes after engulfment than was the parent strain.…”
Section: Discussionmentioning
confidence: 95%